Listening Over Time: Single-Trial Tonic and Phasic Oscillatory Alpha-and Theta-Band Indicators of Listening-Related Fatigue - Hunter, Cynthia R. (Frontiers in Neuroscience, 2022)
Objectives Listening effort engages cognitive resources to support speech understanding in adverse listening conditions, and leads to fatigue over the longer term for people with hearing loss. Direct, neural measures of listening-related fatigue have not been developed. Here, event-related or phasic changes in alpha and theta oscillatory power during listening were used as measures of listening effort, and longer-term or tonic changes over the course of the listening task were assessed as measures of listening-related fatigue. In addition, influences of self-reported fatigue and degree of hearing loss on tonic changes in oscillatory power were examined. Design Participants were middle-aged adults (age 37–65 years; n = 12) with age-appropriate hearing. Sentences were presented in a background of multi-talker babble at a range of signal-to-noise ratios (SNRs) varying around the 80 percent threshold of individual listeners. Single-trial oscillatory power during both sentence and baseline intervals was analyzed with linear mixed-effect models that included as predictors trial number, SNR, subjective fatigue, and hearing loss. Results Alpha and theta power in both sentence presentation and baseline intervals increased as a function of trial, indicating listening-related fatigue. Further, tonic power increases across trials were affected by hearing loss and/or subjective fatigue, particularly in the alpha-band. Phasic changes in alpha and theta power generally tracked with SNR, with decreased alpha power and increased theta power at less favorable SNRs. However, for the alpha-band, the linear effect of SNR emerged only at later trials. Conclusion Tonic increases in oscillatory power in alpha- and theta-bands over the course of a listening task may be biomarkers for the development of listening-related fatigue. In addition, alpha-band power as an index of listening-related fatigue may be sensitive to individual differences attributable to level of hearing loss and the subjective experience of listening-related fatigue. Finally, phasic effects of SNR on alpha power emerged only after a period of listening, suggesting that this measure of listening effort could depend on the development of listening-related fatigue.